VALIDITAS AS-SUNNAH SEBAGAI SUMBER AJARAN ISLAM OTENTIK DAN OTORITATIF (ANALISIS PEMIKIRAN HADIS MUHAMMAD MUSTHAFA AZAMI) - Alwi Bani Rakhman (Jurnal Studi Hadis Nusantara, 2023)
The study of the authenticity, as well as the authority of as-Sunnah as a sourceof Islamic teachings (mashdar at-tasyrî’ al-Islâmiy), has become one of the mostimportant discussions in the study of hadith. Almost of all Muslims have acceptedthe existence of as-Sunnah and juxtaposed it with the Qur'an. But some skepticorientalists and a few communities of Muslims, doubted its validity, and even didn’trecognize it. Through a historical approach, Azami tries to answer these doubtsby doing important research, mostly as a counterattack on the thesises by thoseskepticizes. Through the content analysis from various sources of primary documentsby Azami, it can be concluded descriptively that the validity of As-Sunnah as anauthentic and authoritative source of Islamic teachings can be constructed in amore accurate and scientific manner through a comprehensive understanding ofseveral important relevant points, namely the conceptual formulation of As-Sunnah,the role and position of the Prophet Muhammad in Islam, as well as exploration ofthe historicity elements of As-Sunnah based on explanations of the history of hadithwriting and the isnād system.